2016
DOI: 10.1186/s41240-016-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of physicochemical factor and fecal pollution in the Hansan-Geojeman area, Korea

Abstract: The seasonal variation of fecal coliforms (FCs) and physicochemical factors was determined in seawaters of the Hansan-Geojeman area, including a designated area for oyster, and in inland pollution sources of its drainage basin. The mean daily loads of FCs in inland pollution sources ranged from 1.2 × 10 9 to 3.1 × 10 11 most probable number (MPN)/day; however, the pollutants could not be reached at the designated area. FC concentrations of seawaters were closely related to season, rainfall, and inland contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Measurement of the decomposition rate of sedimentary organic matter is beyond the scope of the present study. No severe hypoxic events were observed throughout the year in the bottom layer of the Geoje–Hansan Bay [ 34 , 35 ], probably reflecting the low biodeposition rates of the oysters, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of the decomposition rate of sedimentary organic matter is beyond the scope of the present study. No severe hypoxic events were observed throughout the year in the bottom layer of the Geoje–Hansan Bay [ 34 , 35 ], probably reflecting the low biodeposition rates of the oysters, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Water depth ranges from 6.5 m in the inner bay to 27.9 m in the outer water channel. Monthly mean water temperatures vary from 9.0 to 25.6°C at the surface layer and from 9.0 to 21.1°C at the bottom layer [ 34 ]. Monthly mean salinities fall within very narrow ranges of 29.5 to 34.2 at the surface layer and 32.8 to 34.2 at the bottom layer.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that bivalves can concentrate fecal-associated pathogenic bacteria from the surrounding water in their bodies, so their consumption poses a risk to human health [73][74][75][76]. Each year, the consumption of contaminated seafood, including shellfish, is implicated in outbreaks of food poisoning caused by pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…In summer, the fecal coliform levels at these stations were affected by rainfall. Other researchers have reported that reductions in fecal coliform concentrations within coastal water from wastewater discharges were attributed to dilution, removal, death, or sedimentation (Chigbu et al 2005;Azalea et al 2010;Park et al 2016). After fecal coliform bacteria are transported into the sea area via runoff, their loss rates from the water column depend on a multitude of factors, including nutrient availability, temperature, salinity, turbidity, degree of water mixing, solar radiation, predation and competition (Chigbu et al 2005).…”
Section: Spatial Distribution Of Fecal Coliform Concentrations In Seamentioning
confidence: 99%
“…A large amount of inland wastewater is discharged into near-shore waters, delivering fecal-associated microorganisms such as fecal coliforms, Salmonella spp., and viruses (Biancani et al 2012;Mok et al 2016a;Park et al 2016). Bivalves are filter-feeding animals that concentrate fecal-associated pathogenic bacteria from the surrounding water in their body, so that consumption of bivalves from polluted waters presents a risk to human health (Azalea et al 2010;Mok et al 2016b;Park et al 2016). Each year, consumption of contaminated seafood including bivalves is implicated in food-poisoning outbreaks caused by pathogenic microorganisms in Korea (Korea Ministry of Food and Drug Safety (KMFDS) 2016).…”
Section: Introductionmentioning
confidence: 99%